ECM-mimicking composite hydrogel for accelerated vascularized bone regeneration - Guanglong Li; Fei Gao; Donglei Yang; Lu Lin; Weijun Yu; Jiaqi Tang; Ruhan Yang; Min Jin; Yuting Gu; Pengfei Wang; Eryi Lu (Bioactive Materials)
Bioactive hydrogel materials have great potential for applications in bone tissue engineering. However, fabrication of functional hydrogels that mimic the natural bone extracellular matrix (ECM) remains a challenge, because they need to provide mechanical support and embody physiological cues for angiogenesis and osteogenesis. Inspired by the features of ECM, we constructed a dual-component composite hydrogel comprising interpenetrating polymer networks of gelatin methacryloyl (GelMA) and deoxyribonucleic acid (DNA). Within the composite hydrogel, the GelMA network serves as the backbone for mechanical and biological stability, whereas the DNA network realizes dynamic capabilities (e.g., stress relaxation), thereby promoting cell proliferation and osteogenic differentiation. Furthermore, functional aptamers (Apt19S and AptV) are readily attached to the DNA network to recruit bone marrow mesenchymal stem cells (BMSCs) and achieve sustained release of loaded vascular endothelial growth factor towards angiogenesis. Our results showed that the composite hydrogel could facilitate the adhesion of BMSCs, promote osteogenic differentiation by activating focal adhesion kinase (FAK)/phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt)/β-Catenin signaling pathway, and eventually enhance vascularized bone regeneration. This study shows that the multifunctional composite hydrogel of GelMA and DNA can successfully simulate the biological functions of natural bone ECM and has great potential for repairing bone defects.